Field Evaluation of Bt. Cotton Hybrids Against Leaf Hoppers and Alternaria Leaf Spot - Durga Prasad, N. V. V. S.; Bhattiprolu, S. L.; Reddy, V. Chenga (International Journal of Bio-resource and Stress Management, 2017)
Bt. cotton, transgenic to protect from boll worms, needs integrated pest/disease management to avoid the losses due to sucking pests and foliar diseases. It is important to identify Bt. cotton hybrids resistant to major pests and diseases. One hundred and forty three Bt. cotton hybrids were evaluated against leaf hopper incidence and Alternaria leaf spot diseases under unprotected conditions during kharif, 2012. The experiment was laid in randomized block design, with two replications, by adopting 105×60 cm2 spacing. Leaf hopper counts were taken at regular intervals and grading was done at peak incidence. Alternaria leaf spot disease was recorded by adopting 0 to 4 scales and percent disease intensity was calculated. Hybrid wise yield was recorded. Two hybrids viz., Tulasi-144 (Prachanda Bhaskar) BG-II (3.75PDI) and U5-SS-33 BG-II (4.38PDI) recorded resistant reaction while 127 hybrids were moderately resistant to Alternaria leaf spot. Fifteen hybrids viz., SWCH-4746 BG-II, Sri Tulasi BG-II-4, NCS 9605, SP 7149, Big boss, ACH-111–2, PCH 468, NCS-456, NCS-245, KSPL (KDCHH-065), NCS-9015 (Malini), Jodha, Lotus, Bunny and Badhra recorded moderate susceptibility. Thirty hybrids exhibited grade II reaction to leaf hoppers including Jadoo KCH-14K-59, Neeraja MRC-7201, ATM-KCH-311 BG-II, Yuva BG II, Dr. Brent MRC-7347 BG-II with moderate resistance to Alternaria leaf spot and yields above 20 q ha-1. In conclusion farmers are advised to cultivate Bt. hybrids with multiple disease resistance to reduce the cost of plant protection and thus net returns can be enhanced.